A General Synthesis of Soft Magnetic 2:17‐Type Rare‐Earth Cobalt Nanoalloys Decorated with Graphite as High‐Frequency Electromagnetic Materials - Ma, Jie; Li, Zhenyang; Tian, Hao; Yang, Bai; Yuan, Yingbo; Li, Ran; Yu, Ronghai (Advanced functional materials, 2024)
A general approach is reported to fabricate a series of single‐phase 2:17‐type rare‐earth cobalt (RE2Co17, RE = Y, Ce, Pr, Nd, and Gd) nanoalloys by precisely controlled calcium thermic reduction of amorphous RE‐Co precursors. High‐purity hexagonal RE2Co17 phases are formed without the precipitation of Co and the other RE‐Co phases through the accurately manipulated co‐reduction of the two ions, which avoids the disadvantages of the impurity or second phases for RE metal alloys. RE2Co17/graphite nanostructures constructed with flower‐like RE2Co17 nanoalloys superficially decorated with nanosized graphite are further fabricated by introducing graphene oxides into the co‐reduction process. Compared with traditional magnetic planar‐anisotropy RE2Co17 alloys, the preserved high saturation magnetization (51.2–102.9 A m2 kg−1) and unusually increased coercivity (152–310.5 Oe) are achieved in these graphite‐decorated RE2Co17 nanoalloys. Moreover, these RE2Co17/graphite nanostructures exhibit good microwave absorption with an applied frequency range of 11.76–18 GHz, which shows their potential applications as new‐type Ku‐band electromagnetic materials. This work provides a facial way for the large‐scale production for varieties of single‐phase 2:17‐type RE‐Co nanoalloys and expands their application fields by constructing novel composite structures. This work provides a universal approach to fabricating a series of soft magnetic 2:17‐type rare‐earth cobalt nanoalloys decorated with graphite (RE2Co17/graphite, RE = Y, Ce, Pr, Nd, and Gd). The well‐structured RE2Co17/graphite nanostructures exhibit good microwave absorption with an applied frequency range of 11.76–18 GHz, which shows their potential applications as new‐type Ku‐band electromagnetic materials.